2016
DOI: 10.1371/journal.pone.0147490
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Effects of Estrogenic Pesticides at the Human Estrogen Receptor α and β

Abstract: Consumers of fruits and vegetables are frequently exposed to small amounts of hormonally active pesticides, some of them sharing a common mode of action such as the activation of the human estrogen receptor α (hERα) or β (hERβ). Therefore, it is of particular importance to evaluate risks emanating from chemical mixtures, in which the individual pesticides are present at human-relevant concentrations, below their corresponding maximum residue levels. Binary and ternary iso-effective mixtures of estrogenic pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The usage of receptor-based reporter assays has been established for the quantitative assessment of chemical mixture effects, especially for substances binding to hormone receptors, by means of concentration addition for substances sharing a mode of action (MoA) or independent action for substances with dissimilar MoA (Orton et al 2014;Seeger et al 2016). This system has also been used in the present study and was again capable of showing that the substances used follow the DA/CA model.…”
Section: Relevance Of Omics Data For Risk Assessment Of Pesticide MIXmentioning
confidence: 99%
“…The usage of receptor-based reporter assays has been established for the quantitative assessment of chemical mixture effects, especially for substances binding to hormone receptors, by means of concentration addition for substances sharing a mode of action (MoA) or independent action for substances with dissimilar MoA (Orton et al 2014;Seeger et al 2016). This system has also been used in the present study and was again capable of showing that the substances used follow the DA/CA model.…”
Section: Relevance Of Omics Data For Risk Assessment Of Pesticide MIXmentioning
confidence: 99%
“…One focus of research on mixture effects of pesticides has been endocrine disruption (Hass et al 2012 ; Orton et al 2011 ; Seeger et al 2016 ). Since the liver is the main target organ of many pesticides, potential hepatotoxic mixture effects are of high relevance.…”
Section: Introductionmentioning
confidence: 99%
“…A dramatic enhancement of endocrine effects not predicted from tests on individual compounds (Rajapakse et al, 2002;Silva et al, 2002Silva et al, , 2011 has been observed for some estrogenic chemicals. When three estrogenic test systems were used (Seeger et al, 2016), similar outcomes on mixtures of endocrinedisrupting pesticides were confirmed. The additive/synergistic behavior of endocrine disruptors is likely to be the case with glyphosate and additives in glyphosate-based formulations.…”
Section: The Underlying Principles Of Adjusting Glyphosate Adi Valuesmentioning
confidence: 76%